Pengaruh Net Profit Margin Dan Total Asset Turnover Terhadap Harga Saham pada PT. AKR corporindo, Tbk - Jamaluddin, Andi; Alam, Andi Rifqah Purnama; Azizah, Amplya Ayu (Jurnal Online Manajemen ELPEI, 2025)
This research aims The aim of this research is to determine the influence of Net Profit Margin and Total Asset Turnover on share prices at PT. AKR Corporindo, Tbk. The types of data used in this research are qualitative data and quantitative data. The data source used in this research is secondary data. The analytical method used in this research is multiple linear regression. From the research results, the results of the multiple linear regression equation were obtained with the equation value Y = - 3281.28 + 147.59X1 + 4783.54X2, the coefficient of determination (R2) was 0.54 and the correlation coefficient (r) was 0.73. Thus, it can be concluded that simultaneously the variables Net Profit Margin and Total Asset Turnover do not have a significant effect on share prices at PT. ACR. Corporindo, Tbk. Partially, the Net Profit Margin variable has no significant effect on share prices at PT. AKR. Corporindo, Tbk and partially the Total Asset Turnover variable have a significant effect on share prices at PT. ACR. Corporindo, Tbk. Thus, the first and second hypotheses are rejected and the third hypothesis is accepted.